1999
DOI: 10.1016/s0924-9338(99)00174-1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal influences on admissions for affective disorder and schizophrenia in Ireland: a comparison of first and readmissions

Abstract: Although genetic and environmental factors operating before or around the time of birth have been demonstrated to be relevant to the aetiology of the major psychoses, a seasonal variation in the rates of admission of such patients has long been recognised. Few studies have compared first and readmissions. This study examined for seasonal variation of admission in the major psychoses, and compared diagnostic categories by admission status. Patients admitted to Irish psychiatric inpatient facilities between 1989… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 31 publications
2
38
0
Order By: Relevance
“…Studies concerning hospitalizations of schizophrenic patients are conflicting. A seasonal variation has been reported with a summer peak in all admissions (Clarke et al 1999;Shiloh et al 2005) or in the first admission (Takei et al 1992); other studies show a correlation between hospitalizations and early spring (Tian et al 2006) or winter (Davies et al 2000). Lastly, no seasonal pattern has been found by several authors (Modai et al 1994;Amr & Volpe 2012).…”
Section: Objectivementioning
confidence: 95%
“…Studies concerning hospitalizations of schizophrenic patients are conflicting. A seasonal variation has been reported with a summer peak in all admissions (Clarke et al 1999;Shiloh et al 2005) or in the first admission (Takei et al 1992); other studies show a correlation between hospitalizations and early spring (Tian et al 2006) or winter (Davies et al 2000). Lastly, no seasonal pattern has been found by several authors (Modai et al 1994;Amr & Volpe 2012).…”
Section: Objectivementioning
confidence: 95%
“…One of the few studies analyzing this indicated that in BPAD, first admission and readmission show a seasonal pattern. However, in schizophrenia, only first admissions show a seasonal peak (41). Alternatively, other studies found seasonality in chronic, not in FE, patients with schizophrenia (42).…”
Section: Introductionmentioning
confidence: 92%
“…[1][2][3][4][5] However, the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) includes the specifier "with seasonal pattern" only for depression. 6 Thus, patients cannot be classified as having "seasonal" affective disorder if their manic episodes occur in a particular season but they do not have seasonal depression.…”
mentioning
confidence: 99%